Experimental investigations on the performance of a single slope solar still coupled with flat plate solar collector under Malaysian conditions / Zainal Abidin Kamarul Baharin and Muhammad Hafiz Mohammad - Kamarul Baharin, Zainal Abidin; Mohammad, Muhammad Hafiz (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The high salinity level of seawater prevents it from being ingested by humans. Desalination using solar energy is a cheaper alternative compared to fossil fuels and it is also renewable and environmentally friendly. The productivity of passive solar stills however is relatively low. Active stills where extra thermal energy is supplied to the water in the evaporator basin using various devices tend to have higher levels of productivity. This paper aims to investigate the performance of a single slope solar still coupled with flat plate solar collector of different design parameters under Malaysian conditions. Results of the experiments showed that the performance of stills coupled with the solar collector is better than the one without. The still with 5 mm copper rods solar collector yielded the highest volume of fresh water (12.5 percent) which is twice the amount produced by the passive still (6.25 percent).